Compressive mechanical behavior and constitutive model of polyvinyl chloride elastomer under dynamic loading - Jingfa Lei; Meng Xu; Tao Liu; Yan Xuan; Hong Sun; Zhan Wei (AIP Advances, 2020)
The mechanical properties of polyvinyl chloride (PVC) elastomers under dynamic loading restrict the service life of PVC products, affecting the product life cycle cost. In order to elucidate the dynamic mechanical properties of PVC elastomers, quasi-static compression tests are conducted at three different strain rates (0.001 s−1, 0.01 s−1, and 0.1 s−1), along with compression relaxation tests at a strain of 0.35. Dynamic compression experiments are also conducted using a split Hopkinson pressure bar experimental device at three different strain rates (1510 s−1, 2260 s−1, and 3000 s−1). Then, a visco-hyperelastic constitutive model consisting of a Yeoh hyperelastic model and rate-dependent viscoelastic model is built based on the experimental data. The order of the relaxation function for the viscoelastic part is determined from the experimental relaxation data, while the model parameters are determined from the experimental quasi-static and dynamic compression data. The results revealed that the PVC elastomer is sensitive to the strain rate, showing obvious visco-hyperelastic behavior. The proposed model accurately describes the mechanical behavior of the PVC elastomer under dynamic loading. This model is expected to provide basic information to support the development and application of PVC elastomer materials.